COPYRIGHT LAW PROTECTION AGAINST ILLEGAL SALES OF WETV STREAMING SUBSCRIPTION ACCOUNTS THROUGH SHOPEE MARKETPLACE - Billa, Adinda Aneke Putri Zalza; Permanasari, Lolita (jfpublisher, 2023)
WeTV is the owner of copyright in computer programs, which has been regulated in Law No. 28/2014 on Copyright. However, there are irresponsible people who violate it by duplicating, distributing and selling WeTV subscription accounts through Shopee marketplace and taking advantage of the benefits personally. It becomes an issue related to copyright protection based on the law on an application program that is being misused by other parties. The method in this research is normative juridical research, which conducts research by analyzing and a series of formal legal rules, including laws and regulations, and literature that contains theoretical concepts. The result of this research that WeTV is an intellectual work in a computer program that is protected by copyright. The sales transaction of WeTV subscribed accounts on the Shopee marketplace by “Mavelstore.id” has a non-authorized method in accordance with the terms and conditions of WeTV. Unauthorized distributors copy without permission from copyright holders and benefit from sales through the Shopee marketplace. The account was found to have committed acts of piracy that caused losses to the WeTV copyright holders. The seller has shared account actions by changing the provision that 1 (one) WeTV user account can only be used by 1 (one) user, to 1 (one) WeTV user account can be used by multiple users. The existence of moral and economic loss is provided an order for the infringement of the creation through the formal procedure of copyright protection efforts against the illegal sales of WeTV accounts through internal legal protection and external legal protection.